Oral microflora in children with hematologic malignancies - M. F. Vecherkovskaya; G. V. Tets; B. V. Afanasiev; V. V. Tets (Онкогематология)
The goal was a comprehensive study of oral microflora in healthy children and those with hematologic malignancies, based on the analysis of mixed microbial biofilms composition, isolation and identification of new previously unknown microorganisms. The material was obtained in children with hematological diseases in remission, 2–10 years aged, and for the control group from St. Petersburg schoolchildren and in kindergartens. We used microbiological, biochemical and molecular genetic methods, including electron microscopy, proteomic analysis, sequencing and complete genome annotation. Microorganisms of 23 genera isolated as pure cultures and identified by biochemical activity from mixed microbial biofilm derived from saliva of healthy and sick children. In microflora of children with hematologic malignancies a previously unknown type of streptococci with a large number of antibiotic resistance genes was revealed. Differences in oral microbiota composition of healthy children and children with hematological diseases in remission were revealed. The microbiota of children with hematologic malignancies contains more genes controlling antibiotic resistance. Also, it was observed previously unknown bacterium of the genus Streptococcus.